Web database applications with PHP MySQL - Williams, Hugh E. (O'Reilly, 2004)
There are many reasons for serving up dynamic content from a web site: to offer an online shopping site, create customized information pages for users, or just manage a large volume of content through a database. Anyone with a modest knowledge of HTML and web site management can learn to create dynamic content through the PHP programming language and the MySQL database. This book gives you the background and tools to do the job safely and reliably.